Unemployment, Education, Poverty, and Inclusive Growth: Evidence from Provinces in Indonesia - Andrian, Tommy (International Journal of Psychosocial Rehabilitation, 2020)
The-aim of-this study-was to examine the effects of-unemployment, education and poverty on inclusive growth. The panel data used in this study are a composite of-time series for the study time from 2015 to 2018 with a cross section in the form of data on per capita expenditure per household and month, total unemployment, net enrollment rates and the number of poor people at the provincial level Indonesia. The former data in this study are secondary data obtained-from the Central Statistics Agency on the website www.bps.go.id. The aftermath of-this study show that (1) unemployment significantly affects inclusive growth, (2) education significantly affects inclusive growth, (3) poverty significantly affects inclusive growth.